Aptidão física relacionada à saúde de crianças e adolescentes paranaenses : dados do PROESP-BR de 2004 a 2010 - Vilauta, Cleide Marlene (2012)
This is a cross-sectional descriptive study aimed at analyzing the variables of physical fitness related to the health of children and adolescents assessed by the battery of tests of Projeto Esporte Brasil, (PROESP-BR). The sample consisted of 8114 children and teens; 4112 females and 4002 males at the ages between 7 and 15 years old. All of them were registered at the PROESP-BR in the State of Paraná. Data were available in a database from the BR-PROESP between the years 2004 and 2010 and involved measurements and physical fitness tests related to health (AFRS) such as: cardiorespiratory endurance, resistance/abdominal strength, flexibility and body mass index. Relative and absolute frequencies, two-way ANOVA and Pearson correlation were used for data analysis (P <0.05). The anthropometrical results as well as resistance / abdominal strength the cardiorespiratory endurance, were in favor of boys at most ages except for flexibility, where the values were in favor of girls at all ages, the BMI were in favor the of girls from 7 to 11 years the favor of boys from 12 to 15 years. In the test of resistance/abdominal strength it was found a significant difference of the younger ages comparing to the older ones in both sexes and at age 15 the girls didn't show difference with any other age. In relation to flexibility there was a significant difference only of the ones who are nine years old compared to the ones who are eleven, in both sexes. In the cardiorespiratory endurance the girls showed significant differences from 10 to 14 years old related to the ones at the age of 15 while the boys showed significant difference of the younger ones compared to the older ones. The percentage of not meeting the criteria of health according to PROESP-BR (2009) which are indicators of a recommended AFRS were presented to girls and boys respectively as follows: BMI (21.7%, 20.3%), test of resistance / abdominal strength (28.7%, 32.3%), flexibility (29.2%, 46.3%) and cardiorespiratory endurance (53.6 %, 49.8%). Most of the correlations found among the AFRS components were low (positive and negative) statistically significant in both sexes. Therefore, since the results, it appears necessary interventions in Physical Education and related areas to improve the levels of Health Related Fitness in this population.